THE TRANSITION TO ENGLISH TEACHING: INFLUENCES AND CONSIDERATIONS FOR FOREIGN LANGUAGE EDUCATION AND LANGUAGE PLANNING - Hao, Tran Thi (VNU Journal of Foreign Studies; Vol 34 No 5DO - 10.25073/2525-2445/vnufs.4302, 2018)
Language policy enactment processes are complex, confounded by varied forces and interests, and shaped through negotiations, interpretations and compromise. Working from this perspective, this article examines the transition process of foreign language teachers from teaching other languages to teaching English, and the influences of this process on general foreign language education and language planning. In Vietnam, even though the shift to English teaching from other languages has been noted as a phenomenon, its process with grass-roots changes and potential influences on foreign language policy enactments in the country have not been specifically examined. By employing a case study approach, this article explores the transition process at An Nam University (pseudonym) , one of the universities undergoing the transition process. Drawn from a document, a preliminary survey, interviews with both teachers and leaders and observations, my study concludes that the transition process has an important role with various influences on different aspects in foreign language education in the university and in Vietnam. The study aims to provide fundamental pointers to current language policy implementation in the country as well as to other contexts undergoing similar changes.